BODIPY-Based Fluorescent Probes for Selective Visualization of Endogenous Hypochlorous Acid in Living Cells via Triazolopyridine Formation - Peraya Hiranmartsuwan; Sirilak Wangngae; Jukkrit Nootem; Anyanee Kamkaew; Rathawat Daengngern; Worawat Wattanathana; Kantapat Chansaenpak (Biosensors, 2022)
, respectively. This fluorescence enhancement phenomenon could be the effect from C = N isomerization inhibition due to HOCl-triggered triazolopyridine formation. In cell imaging experiments, these compounds showed excellent biocompatibility toward RAW 264.7 murine live macrophage cells and greatly visualized endogenous HOCl in living cells stimulated with lipopolysaccharide.
Keywords: Molecular Sensors and Ion Detection; Luminescence and Fluorescent Materials; Nanoplatforms for cancer theranostics